MUTU LAYANAN PENDIDIKAN MADRASAH TSANAWIYAH NAHDHATUL ULAMA OGAN KOMERING ULU TIMUR - Riky Permadi (UNISAN JURNAL, 2023)
The purpose of this study was to determine the quality of education at MTs Nahdhatul Ulama Ogan Komering Ulu Timur, which refers to planning, organizing, directing and supervising. The informants consisted of the head of the madrasa, the deputy head of the madrasa, the head of the madrasah committee, the head of the madrasa administration, the guidance and counseling teacher, and the student council chairman. The data obtained after being tested for validity were then analyzed using qualitative analysis. The results showed that education quality management at MTs Nahdhatul Ulama was carried out in a transformative-participation manner by involving all components of the madrasah with reference to four management functions, namely (1) educational planning that refers to clarity of vision and mission, education quality standards, curriculum development, increasing the competence of teaching staff and educational staff, (2) organizing is carried out through the arrangement of human resources and other physical resources so that they can carry out various educational plans that have been decided; (3) direction is carried out in a professional, healthy and dynamic manner through the implementation of work programs that do not only contain academic values (oriented to intelligence, skills, and student academic achievement; (4) supervision is carried out according to standards through monitoring, performance appraisal, coaching by the head of the madrasa, class supervision by supervisors from the Ministry of Religion, by empowering all components of the madrasa including stakeholders to participate in the madrasah quality improvement program.